KESAKSIAN RUKYAT HILAL DALAM KITAB TAZKIRAH BI AL-AKHBAR ‘AN ITTIFAQAT AL-ASFAR KARYA IBN JUBAIR AL-ANDALUSIY DITINJAU DARI PERSPEKTIF FIKIH DAN ASTRONOMI - Nur Aris (Program Studi Hukum Keluarga Islam, 2018)
This research aims to analyze the reports of the rukyat hilal mentionedin the book ar-Rihlah by Ibn Jubair al-Andalusiy. This book is a reportof Ibn Jubari's trip for approximately 3 years to carry out the pilgrimageto the holy land of Mecca. The journey starts from Shawwal 579 AHfrom Andalusia (Spain) and returns to Andalusia in Muharam 582 H.The rukyat report is analyzed by astronomical and fiqh approaches. Anastronomical approach is used to understand the condition of the newmoon when it is proclaimed to determine the level of visibility,measured by theories of hilal visibility. While the fiqh approach is usedto analyze the rukyat position from its normative aspects. These twoapproaches are expected to be able to deduce the visibility of the hilalat that time from the aspects of sharia and its scientific